Community Social Capital in Supporting Ecosystem Recovery in Rawa Kidang of Way Kambas National Park - Christine Wulandari; Lutfi Nur Latifah; Hari Kaskoyo; Yulia Rahma Fitriana; Zeda Erdian; Vinanda Arum Tri Kurniawan; Aryanti Rizki Adinda; Fadela Yunika Sari; Mhd Zaidi (Journal of Multidisciplinary Applied Natural Science, 2025)
Ecosystem recovery plays a central role in environmental and forest conservation efforts, including efforts made in a conservation area that is a national park. This effort requires support from the communities living around the national park. Therefore, the presence of the community can become a form of capital, which is generally referred to as social capital and will determine the success of a program. Elements of social capital consist of trust, norms, and networks is one form of capital that is very valuable in addition to economic capital, physical capital, and human capital. The purpose of this research is to analyze the level of social capital that exists in the community and how the characteristics of respondents affect social capital. This research is located in Labuhan Ratu VII Village, Labuhan Ratu Subdistrict, East Lampung Regency from November to December 2023. Based on the results of the analysis, it is known that the trust element and the social network element are in the medium category, while the norm element is in the high category. Education and length of stay are respondent characteristics that influence community social capital in supporting ecosystem recovery in Rawa Kidang, Way Kambas National Park (WKNP). Increasing social capital can be done through two characteristics that affect community social capital in the form of informal education such as training. People who live for a long time will affect the sustainability of WKNP so training can be carried out for a long period of time in a structured and intensive manner towards sustainable WKNP management. The results of this study can be a consideration for WKNP managers in implementing Permen LHK policy no 14 of 2023 concerning business and/or activity arrangements in nature conservation areas, nature reserve areas and hunting arks because they must have a strong social foundation.